Aldous Huxley: a pioneer of an ecological and pacifist vision - Fortunati, Vita (Cadernos de Literatura Comparada, 2024)
The aim of my paper is to analyse Aldous Huxley’s utopian novel Island (1962) comparing it to the ideas expounded in his essays Science, Liberty and Peace (1946) The Human Situation (1959), The Politics of Ecology-The Question of Survival (1963) An Encyclopaedia of Pacifism (1972). As we shall see, Huxley, in accord with the “green movement” of the Seventies and Eighties (S.F. Schumacher, 1974, H. Daly, 1977, D.W. Pearce, R.K. Turner, 1990) discusses several important issues that are still, today, at the very core of the environmental debate. Aldous Huxley is an interesting example of an intellectual who managed to unite the two cultures, scientific and humanistic, and who dedicated his life to the search of new perspectives and as yet unexplored horizons. His motto “Aùn aprendo” (“I keep learning”) brilliantly exemplifies his lucidly critical attitude towards the reality surrounding him and his observation of nature. His critical thought is a complex combination of rationality and creativity, of scepticism and mysticism that finds its synthesis in the philosophical principle of being “realistically idealist”.